Multikulturalisme dalam Pembelajaran Pendidikan Agama Islam di SMP Bell Kota Surabaya - Ulumuddin, Ihya’; pengelola, pengelola (LPPM STAI Ihyaul Ulum Gresik, 2021)
This study aims to examine three main problems, namely: multicultural values contained in Islamic Education learning; the process of investing multicultural values in Islamic Education Learning; methods of character building through multicultural values in Islamic Education Learning. The study was conducted at SMP BELL Surabaya. Data analysis techniques include data collection, data reduction, data display and conclusion verification. The findings show that multicultural values contained in Islamic Education Learning content include tolerance values, equality values, unity values, kinship values, and justice values. The planting of multicultural values in Islamic Education Learning at SMP BELL Surabaya uses two methods, namely the exemplary method and the habituation method. The impact of planting multicultural values on students is the growth of mutual tolerance, respect, accepting the opinions of others, mutual cooperation, not hostile, and the absence of conflict due to differences in culture, ethnicity, language, customs, and religion.